Reinstatement of "germinal epithelium" of the ovary - Nishida Naoyo; Nishida Takashi (BMC, 2006)
Abstract Background The existing dogma that the former term ovarian "germinal epithelium" resulted from a mistaken belief that it could give rise to new germ cells is now strongly challenged. Discussion Two years ago, a research group of the University of Tennessee led by Antonin Bukovsky successfully demonstrated the oogenic process from the human ovarian covering epithelium now commonly called the ovarian surface epithelium. They showed the new oocyte with zona pellucida and granulosa cells, both originated from the surface epithelium arising from mesenchymal cells in the tunica albuginea, and stressed that the human ovary could form primary follicles throughout the reproductive period. This gives a big impact not only to the field of reproductive medicine, but also to the oncologic area. The surface epithelium is regarded as the major source of ovarian cancers, and most of the neoplasms exhibit the histology resembling müllerian epithelia. Since the differentiating capability of the surface epithelium has now expanded, the histologic range of the neoplasms in this category may extend to include both germ cell tumors and sex cord-stromal cell tumors. Summary Since the oogenic capability of ovarian surface cells has been proven, it is now believed that the oocytes can originate from them. The term "germinal epithelium", hence, might reasonably be reinstated.